Assessment of growth rate, chlorophyll a fluorescence, lipid peroxidation and antioxidant enzyme activity in Aphanizomenon flos-aquae, Pediastrum simplex and Synedra acus exposed to cadmium - Ran, Xiaofei (Ecotoxicology (London, England), 2015)
In this study, the effects of cadmium on the cyanobacterium Aphanizomenon flos-aquae, the green alga Pediastrum simplex and the diatom Synedra acus was evaluated on the basis of growth rate, chlorophyll a fluorescence, lipid peroxidation and antioxidant enzyme activity. The EC50 values (effective concentration inducing 50 % of growth inhibition) of cadmium in A. flos-aquae, P. simplex and S. acus were 1.18 ± 0.044, 4.32 ± 0.068 and 3.7 ± 0.055 mg/L, respectively. The results suggested that cadmium stress decreases growth rate and chlorophyll a concentration. The normalized chlorophyll a fluorescence transients significantly increased at cadmium concentrations of 5.0, 10.0 and 20.0 mg/L, but slightly decreased at concentrations of 0.2, 0.5 and 1.0 mg/L. The chlorophyll fluorescence parameters showed considerable variation among the three species, while lipid peroxidation and antioxidant enzyme activities showed a significant increase. Our results demonstrated that blockage of electron transport on the acceptor side of photosystem II is the mechanism responsible for cadmium toxicity in freshwater microalgae, and that the tolerance of the three species to cadmium was in the order green alga P. simplex > diatom S. acus > cyanobacterium A. flos-aquae